Analysis of Suitability and Carrying Capacity for Marine Ecotourism on Small Islands in West Lombok. (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
The implementation of potential and carrying capacity-based area management is expected to minimize damage to coastal ecosystems so that environmental quality is maintained and visitors can enjoy an optimal tourism experience. Integration between the analysis of suitability and carrying capacity of the area is very important to formulate a sustainable marine ecotourism management strategy. This study analyzes the land suitability and carrying capacity of resource-based marine ecotourism areas on small islands to support sustainable tourism development. The methods used include literature studies, field observations, and in situ measurements of biophysical parameters. Analysis of suitability and carrying capacity is used to determine marine ecotourism in the categories of beach tourism, snorkeling, and diving. The study found that the waters of GITANADA Sekotong, West Lombok, are suitable to very suitable for marine ecotourism development, including beach recreation, snorkeling, and diving, based on the area’s carrying capacity. The carrying capacities for these activities are 295, 155, and 506 persons/day, respectively, with a total capacity of 956 visitors per day within an eight-hour operational period. These findings imply that implementing a visitor quota system and regular monitoring of ecological conditions are essential to ensure the long-term sustainability of marine ecotourism in the GITANADA area.